Efficacy of sarolaner (Simparic™) against induced infestations of Amblyomma cajennense on dogs - Fabio Scott; Lilian Franz; Diefrey Ribeiro Campos; Thaís Ribeiro Correia Azevedo; Daise Cunha; Robert H. Six; Steven Maeder; Travis Cree (Parasites & Vectors, 2017)
Abstract Background Amblyomma cajennense is the main vector of Rickettsia rickettsii which causes Brazilian spotted fever. This adult tick preferably infests horses and capybaras, but has low host specificity during its immature stages, thus posing a threat to humans and dogs. In this study, the efficacy of sarolaner (Simparic™/Simparica®, Zoetis) when administered once orally to dogs at 2 mg/kg was evaluated against induced infestations of A. cajennense nymphs for up to 35 days after treatment. Methods Based on pretreatment tick counts, 20 dogs were randomly allocated to treatment with sarolaner (Simparic™) dosed at 2 mg/kg of body weight or a placebo on Day 0 of the study. Artificial infestations were performed using laboratory raised A. cajennense nymphs on study days -2, 5, 12, 19, 26 and 33. Efficacy was determined at 48 h post-treatment or post-infestation at each time point relative to the counts for dogs that received placebo. Results There were no adverse reactions to treatment. A single dose of sarolaner (Simparic™) provided 100% efficacy on study days 2, 7 and 14; and ≥ 99.6% on days 21, 28 and 35. Geometric mean live tick counts for sarolaner were significantly lower than those for placebo on all days (P < 0.0001). Conclusions Under the conditions of the present study, sarolaner (Simparic™) administered once orally at 2 mg/kg provided 100% efficacy against existing infestations and ≥ 99.6% efficacy within 48 h against weekly challenges of A. cajennense for at least 35 days after treatment.